2002
DOI: 10.1002/art.10306
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Fcγ receptor IIa polymorphism in susceptibility to systemic lupus erythematosus and lupus nephritis: A meta‐analysis

Abstract: Objective. To assess the impact of the Fc␥ receptor type IIa (Fc␥RIIa)-R/H131 polymorphism on the risk for systemic lupus erythematosus (SLE) and development of lupus nephritis.Methods. A meta-analysis was performed based on the Medline and Embase databases (last retrieval August 2001), assessment of bibliographies of pertinent articles, and additional data gathered after contact with primary investigators.Results. A total of 25 comparisons from 17 studies involving R/H131 genotyping of 1,405 patients with lup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
120
2
6

Year Published

2003
2003
2004
2004

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 187 publications
(138 citation statements)
references
References 57 publications
10
120
2
6
Order By: Relevance
“…Our results in the family-based association studies provide supportive evidence for the findings of the metaanalysis of case-control association studies, which demonstrated significant association of FCGR2A-131R (11). On the other hand, we failed to replicate the association of FCGR3A-176F with the presence of lupus nephritis, which was shown in the meta-analysis of FCGR3A (12).…”
Section: Concise Communications 671supporting
confidence: 81%
See 1 more Smart Citation
“…Our results in the family-based association studies provide supportive evidence for the findings of the metaanalysis of case-control association studies, which demonstrated significant association of FCGR2A-131R (11). On the other hand, we failed to replicate the association of FCGR3A-176F with the presence of lupus nephritis, which was shown in the meta-analysis of FCGR3A (12).…”
Section: Concise Communications 671supporting
confidence: 81%
“…Recently, the first family-based association study on FCGR polymorphisms in SLE was reported (10); the authors described significant transmission of FCGR3A-176F in European American and African American SLE families. In addition, recent large-scale meta-analyses of case-control association studies convincingly demonstrated that FCGR2A-131R is an important risk factor for SLE (11), while FCGR3A-176F is associated with the development of lupus nephritis rather than with SLE per se (12).…”
mentioning
confidence: 99%
“…Research teams worldwide working on the low-affinity Fc␥R and their association with autoimmune diseases were invited to contribute data, provided that their study patients met the eligibility criteria defined above. We contacted teams identified as part of a previous meta-analysis that examined the role of the Fc␥RIIA-R/H131 polymorphism in SLE and lupus nephritis (9). Other potentially relevant studies were sought by searches of the Medline and EMBase databases (last search August 2002), with various combinations of key words ("antiphospholipid," "anticardiolipin," "polymorphism," "allele," "genetics," "Fc receptor," and "Fc␥ receptor").…”
Section: Methodsmentioning
confidence: 99%
“…This polymorphism has been proposed to be influential in a variety of autoimmune diseases (7). The low-binding R131 allele imparts a significant risk for systemic lupus erythematosus (SLE) (9). Binding to the H131 variant can initiate more pronounced monocyte, platelet, and endothelial cell activation in the context of an IgG2 immune response, inducing a prothrombotic phenotype.…”
mentioning
confidence: 99%
See 1 more Smart Citation